Comportamiento de las formas de fósforo y sus relaciones con la absorción de P por la avena, bajo tres fuentes de fertilización fosfatada en un latosol de Nariño, Colombia - Ortega E., J.; Guerrero Riascos, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Under greenhouse conditions, it was evaluated by effect of four levels, and three sources of P2O5 on oat production and on the soil P fractions, as well as the interactions of these factions with the absorption of P by the plant. The soil used was a latosol from the Pacific coasts of Nariño, Colombia. The levels of P2O5 linearly and significantly increased dry matter production, P absorption, non-apatitic calcium phosphates and aluminum phosphates. Their effect on the apatitic calcium phosphates was quadratic and on organic-P was cubic. Levels of P205 did not affect iron phosphates. Basic slag and triple superphosphate were equally efficient in supplying P to the plant, largely surpassing phosphoric rock whose effectiveness was nil. The interaction effect of level due to source showed that the precipitation of the added-P into the different P fractions was independent from the source used. The contribution of P forms to P absorption by the plant of operated in the following priority order: P-Al (r = 0.70**) > P-Fe (r = 0.59*) ≥ non apat: P-Ca (r = 0.50) > P-org (r = 0.43) > apat. P-Ca and non-apatitic P-Ca, in the three added sources, was in the following intensity sequence: